Assessment and characterization of sound pressure levels in Portuguese neonatal intensive care units - Santos, Joana (2017)
In NICU, systematic exposure to sound pressure levels above the recommended can affect both neonates and staff. This study aimed to evaluate the sound pressure levels in three Portuguese NICU and the noise perception of staff. The measurements were performed with a sound level meter, considering the location of the main sources of noise and the layout of the units. A questionnaire was applied to assess noise perception of professionals. The staff classified the environment (regarding noise) as ―slightly uncomfortable‖ (41.1%) and 48.4% considered it as ―acceptable‖. In addition, the majority (55.5%) considered ―equipment‖ as the most annoying source of noise. The results showed that noise levels were excessive in all the evaluated areas of the NICUs, exceeding international guidelines, with the levels ranging between 48.7 dBA to 71.7 dBA. Overall, there is a need for more research in order to verify the effectiveness of some actions and strategies to reduce the impact of noise in NICU.